Conformation‐Enabled Total Syntheses of Ohmyungsamycins A and B and Structural Revision of Ohmyungsamycin B. Issue 12 (21st February 2018) - Hur, Joonseong; Jang, Jaebong; Sim, Jaehoon; Son, Woo Sung; Ahn, Hee‐Chul; Kim, Tae Sung; Shin, Yern‐Hyerk; Lim, Changjin; Lee, Seungbeom; An, Hongchan; Kim, Seok‐Ho; Oh, Dong‐Chan; et al.
Abstract: The first total syntheses of the bioactive cyclodepsipeptides ohmyungsamycin A and B are described. Key features of our synthesis include the concise preparation of a linear cyclization precursor that consists of N ‐methyl amides and non‐proteinogenic amino acids, and its macrolactamization from a bent conformation. The proposed structure of ohmyungsamycin B was revised based on its synthesis. The cyclic core of the ohmyungsamycins was shown to be responsible for the excellent antituberculosis activity, and ohmyungsamycin variants with truncated chains were evaluated for their biological activity. Abstract : Turn by turn : The first total syntheses of the bioactive cyclodepsipeptide ohmyungsamycin A and the proposed structure of ohmyungsamycin B are based on the concise preparation of a linear cyclization precursor followed by macrocyclization. In addition, the proposed structure of ohmyungsamycin B was revised, and the correct position of the additional methyl group was elucidated.